2004
DOI: 10.1637/7095
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Factors, Environmental Contaminants, and Parasites of White-Tailed Sea Eagles from Greenland

Abstract: Twelve white-tailed sea eagles (Haliaeetus albicilla groenlandicus) found dead between 1997 and 2000 in Greenland were examined to investigate the health status, including the causes of death and the burden of organochlorine contaminants and potentially toxic heavy metals. The determined causes of death were unspecific trauma (n = 6), lead poisoning (n = 2) with 36 and 26 ppm lead in the liver tissue, infectious diseases (n = 1), injuries sustained during intraspecific conflict (n = 1), and gunshot (n = 1). On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…Wendell et al (2002) identified toxicosis as the primary cause of death in about 2% of the birds, which is fairly consistent with data published by the SAGIR network regarding game species (Lamarque et al, 1999). In White-tailed Sea Eagles (Haliaeetus alvicilla) in Greenland, one case of lead poisoning was identified among 12 reported deaths (Krone et al, 2004). Considering the limited number of birds included in this series, the proportion of poisoning cases (8%) may not be significant.…”
Section: Discussionmentioning
confidence: 90%
“…Wendell et al (2002) identified toxicosis as the primary cause of death in about 2% of the birds, which is fairly consistent with data published by the SAGIR network regarding game species (Lamarque et al, 1999). In White-tailed Sea Eagles (Haliaeetus alvicilla) in Greenland, one case of lead poisoning was identified among 12 reported deaths (Krone et al, 2004). Considering the limited number of birds included in this series, the proportion of poisoning cases (8%) may not be significant.…”
Section: Discussionmentioning
confidence: 90%
“…The white-tailed sea eagle (Haliaeetus albicilla) and the threatened Spanish imperial eagle (Aquila adalberti) are species that are affected by lead toxicity (Hernández 1995;Krone et al 2004;Helander et al 2009). Numerous authors have presented lead risk to raptors in Spain, including predators and scavengers (Mateo et al 2001;Perez-Lopez et al 2008;Hernández and Margalida 2009;Mateo 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We tried to minimize this source of bias by using tissues of birds (1) that died of several different causes of death (Krone et al . , , ) and (2) were in good nutritional condition, i.e. these individuals died quickly and were in all probability not restricted in terms of foraging or capturing prey.…”
Section: Discussionmentioning
confidence: 99%
“…These birds died from a variety of natural and anthropogenic causes (for details regarding the causes of mortality see Krone et al . , , ). Liver and muscle tissue reflect the isotopic composition of resources incorporated over a few days to 2 weeks and from 2 weeks to 1 month, respectively (Martínez del Rio et al .…”
Section: Methodsmentioning
confidence: 99%